Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 3 - 3.1 - Quadratic Functions and Models - 3.1 Exercises - Page 250: 81



Work Step by Step

$x=\frac{-b±\sqrt {b^2-4ac}}{2a}$ $x_1=-\frac{b}{2a}+\frac{\sqrt {b^2-4ac}}{2a}$ $x_2=-\frac{b}{2a}-\frac{\sqrt {b^2-4ac}}{2a}$ The average of the zeros: $\frac{x_1+x_2}{2}=\frac{-\frac{b}{2a}+\frac{\sqrt {b^2-4ac}}{2a}-\frac{b}{2a}-\frac{\sqrt {b^2-4ac}}{2a}}{2}=\frac{-\frac{b}{a}}{2}=-\frac{b}{2a}$ Also the x-coordinate of the vertex is: $-\frac{b}{2a}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.